(untitled) (Journal of Contemporary Studies, 2025)
This paper examines the discourse surrounding climate change at COP27 through the lens of Postcolonial Critical Discourse Analysis (PCDA), which combines insights from Postcolonial Theory and Critical Discourse Analysis. Using the frameworks of Fairclough, Dryzek, and Van Dijk, the study analyses speeches from the UNFCCC Secretariat, the European Union, and the Umbrella Group to explore representations of the Global South, recognizes historical responsibility, and equity in climate negotiations. The findings reveal that while the UNFCCC Secretariat emphasizes inclusivity and transparency, the EU and the United States often reinforce colonial hierarchies by framing themselves as global leaders and neglecting the agency of marginalized communities. This study underscores the necessity of decolonizing climate negotiations to achieve equitable and effective global climate action. It calls for recognizing historical injustices, valuing indigenous knowledge, and promoting the Global South’s active role in addressing the climate crisis.